Association between ACYP2 polymorphisms and the risk of renal cell cancer. Issue 11 (5th September 2019) - Wang, Yuhe; Zhang, Yongtong; Sun, Yao; Wu, Jiamin; Chang, Junke; Xiong, Zichao; Niu, Fanglin; Gu, Shanzhi; Jin, Tianbo
Abstract: Background: Kidney cancer is the predominant form of malignancy of the kidney and accounts for approximately 3%–4% of all cancers. Renal cell cancer (RCC) represents more than 85% of kidney cancer. It has been reported that genetic factors may predispose individuals to RCC. This study evaluated the association between Acylphosphatase 2 ( ACYP2 ) gene polymorphisms and RCC risk in the Han Chinese population. Methods: Twelve single‐nucleotide polymorphisms (SNPs) in ACYP2 were genotyped using the Agena MassARRAY platform from 293 RCC patients and 495 controls. The Chi‐squared test, genetic models, haplotype, and stratification analyses were used to evaluate the association between SNPs and the risk of RCC. The relative risk was estimated using the odds ratio (OR) and 95% confidence interval (CI). Results: We observed that the rs6713088 allele G (OR = 1.26, 95% CI: 1.03–1.53, p =  .023) and rs843711 allele T (OR = 1.29, 95% CI: 1.06–1.57, p =  .010) were associated with increased RCC risk. Genetic model analyses found that rs843711 was significantly associated with an increased RCC risk under the recessive model and log‐additive model after adjusting for age and gender. Haplotype analysis showed that the haplotype "TTCTCGCC" (OR = 0.67, 95% CI: 0.48–0.94, p =  .021) was associated with a decreased risk of RCC in the Han Chinese population. Stratification analysis also found that rs6713088 and rs843711 were significantly associated with increased RCC risk. Conclusion: In summary, the results suggested that ACYP2 polymorphisms could be used as a genetic marker for RCC. Additional functional and association studies are required to validate our results. Abstract : Twelve single‐nucleotide polymorphisms (SNPs) in ACYP2 were genotyped using the Agena MassARRAY platform from 293 RCC patients and 495 controls. The results suggested that ACYP2 polymorphisms could be used as a genetic marker for RCC. Additional functional and association studies are required to validate our results.